2020
DOI: 10.1093/chemse/bjaa068
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Odor Mixtures in the Dog Brain: An Awake fMRI Study

Abstract: In working and practical contexts, dogs rely upon their ability to discriminate a target odor from distracting odors and other sensory stimuli. Using awake fMRI in 18 dogs, we examined the neural mechanisms underlying odor discrimination between two odors and a mixture of the odors. Neural activation was measured during the presentation of a target odor (A) associated with a food reward, a distractor odor (B) associated with nothing, and a mixture of the two odors (A+B). Changes in neural activation during the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
2
6
0
Order By: Relevance
“…Areas across the anterior (GI, XMII), medial (LM) and posterior (LPDI, LPVI, LPVII) cingulate gyrus are all found among the most central nodes, next to the prorean gyrus and splenial gyrus. Functional dog fMRI studies also report the involvement of the cingulate gyrus across several tasks, such as word detection and odour discrimination (Prichard et al 2018(Prichard et al , 2020 The cingulate cortex plays a central role in various functions related to behavioural flexibility, ranging from autonomic regulation to action selection and performance monitoring. It is a processing hub for the regulation of autonomic responses, assessing emotional and motivational aspects of internal and external information (seeing emotional faces or listening to emotionally charged et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas across the anterior (GI, XMII), medial (LM) and posterior (LPDI, LPVI, LPVII) cingulate gyrus are all found among the most central nodes, next to the prorean gyrus and splenial gyrus. Functional dog fMRI studies also report the involvement of the cingulate gyrus across several tasks, such as word detection and odour discrimination (Prichard et al 2018(Prichard et al , 2020 The cingulate cortex plays a central role in various functions related to behavioural flexibility, ranging from autonomic regulation to action selection and performance monitoring. It is a processing hub for the regulation of autonomic responses, assessing emotional and motivational aspects of internal and external information (seeing emotional faces or listening to emotionally charged et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Functional dog fMRI studies also report the involvement of the cingulate gyrus across several tasks, such as word detection and odour discrimination (Prichard et al. 2018 , 2020 )…”
Section: Discussionmentioning
confidence: 99%
“…One of the advantages of fMRI is the possibility of obtaining a detailed evaluation of the brain’s reaction to a mixture of odors or to identify the particular brain region(s) activated by odors connected with some features (e.g., familiar or unfamiliar odor), studies that would be difficult to carry out using traditional, behavioral methods of examination [ 194 ].…”
Section: Novel Methods Of Canine Olfaction Evaluation—fmri Studymentioning
confidence: 99%
“…Since behavioral reactions are very often ambiguous and difficult to interpret, new methods to evaluate the impact of odors on the chemical signal-receiver are still being proposed. In cases where a strong behavioral reaction is not advisable, such as during EEG or fMRI studies requiring long immobilization, dogs must be trained to not react to the odors presented, since reaction of the particular brain regions is interpreted as a reaction to the olfactory signal [ 62 , 193 , 194 ].…”
Section: Chemical Communication Influencing Animal Behaviormentioning
confidence: 99%
“…An understanding of the neural correlates of olfaction would be vital to a greater understanding of a dog's perception and cognition. Early studies that measured EEG of sedated dogs showed promise in decipherable differences between evoked potentials between stimuli [40] and multiple studies using fMRI have observed meaningful neural correlates from olfactory tasks in dogs [50,89,90].…”
Section: Unexplored Questionsmentioning
confidence: 99%